Effect of therapeutic exercises on the progression of adolescent idiopathic scoliosis: a protocol of a systematic review - Nelson Carvas Junior; Henry Dan Kiyomoto; Ana Paula Ribeiro; Rodrigo Mantelatto Andrade; Milene Eloise Callegari Ferreira; Larissa Piras; Maria De Lourdes Partika Kiyomoto; Silvia Maria Amado João (BMJ Open)
Introduction Adolescent idiopathic scoliosis (AIS) affects an estimated 200 million adolescents globally and curvatures exceeding 30° at skeletal maturity are associated with increased health risks in adulthood. The International Society for the Orthopedic and Rehabilitative Treatment of Scoliosis recommends specific therapeutic exercises to prevent the progression of AIS. However, studies have questioned the effects of specific and general therapeutic exercises on the progression of AIS. This systematic review will evaluate the effectiveness of general and specific therapeutic exercises in preventing Cobb angle progression compared with other conservative interventions.Methods and analysis We will search MEDLINE (via PubMed), EMBASE, CENTRAL, PEDro and CINAHL from inception to 14 December 2023. Randomised clinical trials involving individuals aged 10 to 18 years with a Cobb angle above 10° will be considered. The effectiveness of therapeutic exercises will be compared with minimal intervention, other exercises and brace use, alone or in combination with exercise. The primary outcome is the Cobb angle measurement, with subgroup analyses assessing severity based on SOSORT classifications. The risk of bias will be assessed using the PEDro scale and Grading of Recommendations, Assessment, Development and Evaluation will be used to assess certainty of evidence. The Review Manager 5.4 software will be used for meta-analysis. The protocol follows the Cochrane Handbook for Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols guidelines.Ethics and dissemination This is a literature-based study and ethical approval is not required. The findings will be disseminated through peer-reviewed publications.PROSPERO registration numberCRD42020156639.